Applications of Wavelet Transform and Wavelet Packet Transform to Detect the Crack in Micro Beams - Ithaya Priya.B, Ravikumar.K, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Micro beams found to be an optimistic device for several applications in various MEMS device like actuators, diaphragms, sensors and accelerometers. Its high sensitivity, accuracy and precision made this to be a basic functional unit of most MEMS devices. Micro beams shows difference in its vibrational frequency, stress and deflection over various input conditions. Occurrence of defects in the miniaturized structure can show major impact in its performance and sensitivity. Hence it is very essential to detect any defects presents in the micro device structure. In this study an eminent method of identifying the presence of cracks and its exact locations by interpreting the change in deflection and stress experienced by the micro beam using wavelet transform was illustrated. Wavelet transform and its packet decomposition is one among the efficient mathematical tool for analyzing signals in both frequency and time domain. The proposed device structure was designed and modeled using COMSOL Multiphysics simulation software. From the obtained results the location of the cracks which appears in micro cantilever structure due to various working conditions can be perfectly identified using wavelet transform analysis.